Channel type and substrate influence on aquatic macroinvertebrate abundance and diversity in a montane stream - Mitchell, Emily, author; Wohl, Ellen, advisor; Blehm, Lindsey, committee member (Colorado State University. Libraries, 2025)
Aquatic macroinvertebrate communities respond strongly to changes in their habitat, making them useful indicators of conditions in streams. It is important to understand the relationship between habitat complexity and macroinvertebrate communities, especially as streams become more affected by anthropogenic influences. This study investigates the differences in macroinvertebrate abundance and diversity between primary and secondary channels, as well as cobble and wood substrates. The study took place at Little Beaver Creek, a montane stream in northern Colorado that is relatively undisturbed by humans. Multiple cobble and wood samples were selected from both the main and side channels, and the macroinvertebrates present on each sample were identified to order. These results were analyzed, along with data related to the decay class of the wood samples and the substrate size, using single and multiple linear regression models and the Shannon-Wiener Species Diversity Index. The results indicate that substrate was a significant predictor of total macroinvertebrate density (p = 0.001), while channel location was not (p = 0.9). There were some variations in this result when considering specific taxa. Cobbles had a significantly higher density of individuals than wood, and the side channel had a higher density of individuals than the main channel, although this result was not statistically significant. Shannon index values for the main channel were higher than the side channel (1.48 vs. 1.24). Although some trends were not statistically significant, the results highlight the value of habitat complexity. Maintaining diverse substrate types and multi-channel morphology is necessary to support more robust macroinvertebrate communities.